Kondisi Hidro-Oseanografi dan Sumberdaya Perikanan Perairan Kepulauan Seribu - Sachoemar, Suhendar I.; Amarullah, M. Husni; Aliah, Ratu Siti (Jurnal Hidrosfir Indonesia, 2007)
An evaluation of the hydro-oceanography characteristics and fisheries resources was conducted in the Seribu Island area, an offshore area of the Jakarta Bay. The area was influenced by monsoonal system that affected the oceanography and water quality situation. The bathymetry within this area was a range of 3 – 50 m with shallow water depth in and surround the islands. While the wave, current speed and tidal range were around 0,5-3,0 m; 5-49 cm/sec and 80 cm, respectively. Water quality status was varied among the area and it is depend on the distance from Jakarta Bay. In the middle and upper part of the area, water quality was within the moderate to the excellent and this condition has promoted the area as potential area of fisheries for both fish culture and fishing. As indication, an abundance of the benthic organism (sea urchin), milk fish, reef fish, seaweed and pelagic fish was found within this area. Keywords: Hydro-oceanography, fisheries resources, Kepulauan Seribu